Pembuatan Nomor Induk Berusaha (NIB) Sebagai Upaya Penguatan Usaha Bagi UMKM Di Desa Sumur Mati - Ryan Arsy Hidayatullah; Acep Samsudin (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
The government made a policy where MSME actors were expected to have complete and legal licensing documents. Of the 10 MSME actors listed by the UMKM coordinator in Sumurmati Village, all of them have not been registered and have a Business Identification Number (NIB). Therefore, with the KKN-T MBKM Group 62 UPN "Veteran" East Java in Sumurmati Village, as a form of service to the community, KKN-T MBKM Group 62 created a program where these students will help MSME actors in Sumurmati Village to have a Business Identification Number (NIB) by conducting socialization and also helping these MSME actors to register their businesses through Online Single Submission (OSS). By having complete and legal permits, MSME actors can be protected by law so as to prevent them from legal disputes that can be detrimental to their business, facilitate business development, provide opportunities for them to obtain business assistance or training from the government, and make it easier to obtain venture capital because their businesses already have complete and legal permits.